Sensory acceptability and willingness to buy foods presented as having benefits achieved through the use of nanotechnology. (July 2020) - Kuang, Lina; Burgess, Brenda; Cuite, Cara L.; Tepper, Beverly J.; Hallman, William K.
Highlights: Most young adult consumers liked and were willing to buy foods with nanotechnology benefits. The reasons for buying these foods was 'sensory appeal' and 'nanotechnology benefit'. Surveys revealed mostly positive attitudes towards foods with nano-ingredients. Abstract: Nanotechnology is the manipulation of matter on a small scale (1-billionth of a meter). Nanomaterials have been used extensively in food production and packaging to improve food safety and eating quality. However, consumer knowledge of nanotechnology is low and the public's perceptions about its use in foods is poorly understood. This study assessed consumers' knowledge and attitudes towards food nanotechnology, and measured degree of liking and purchase intent for tasted foods presented as having specific nanotechnology benefits. Participants were 161 young, mostly college-educated adults. They evaluated samples of fresh cherry tomatoes and chocolate ice cream for overall liking and liking of key attributes using 15-cm line scales. They were informed that the first sample of each food had no nanotechnology (control), but the subsequent samples were produced with nanotechnology materials. For the tomatoes, nanoparticles were added to the packaging as an anti-microbial or to extend freshness; for the ice cream, nanoparticles were incorporated into the food matrix to deliver probiotics or reduce icing. In reality, no foods were produced with nanotechnology. Participants also completed surveys on their food attitudes and knowledge of nanotechnology. Results showed that all the samples were highly liked, regardless of whether they claimed to deliver nanotechnology benefits. In addition, most (75–86%) participants were willing to buy the nanotechnology foods; the primary reasons being "sensory appeal" and "nanotechnology benefit" (p < 0.01). These results show that a majority of young, educated consumers had positive attitudes towards foods with nanotechnology and were willing to buy them.